Amino acids in retinitis pigmentosa. Issue 9 (September 1981) - Arshinoff, S A; McCulloch, J C; Macrae, W; Stein, A N; Marliss, E B
Abstract : A survey of fasting whole blood amino acids in 65 patients with various subtypes of retinitis pigmentosa performed. Eight X-linked recessive patients showed decreased taurine and aspartate. Nineteen autosomal recessive patients, and to lesser extent 10 autosomal dominant patients, showed reduced levels of whole blood threonine and histidine. Branched-chain amino acids and arginine were present in increased amounts in 2 patients with Laurence-Moon-Bardet-Biedl syndrome. These findings in LMBB patients are probably related in part to their obesity and emphasise that appropriate controls are required, and other factors (including age) known to affect amino acid levels must be accounted for. The biochemical implications of our findings are not yet apparent.